Cognitive impairment in remitted late-life depression is not associated with Alzheimer's disease-related CSF biomarkers - Loureiro, Júlia C. (2020)
Background: Cognitive impairment is a common feature of late-life depression (LLD). Early studies using Alzheimer's disease (AD) biomarkers inferred a biological link between AD pathology and LLD, but recent findings have challenged this association. The aim of this investigation was to determine a panel of AD-related cerebrospinal fluid (CSF) biomarkers in a cross-section of elders with mild cognitive impairment (MCI) with and without LLD. Methods: Subjects comprised 102 older adults: 27 with ‘pure' amnestic MCI (aMCI), 53 with major depression and cognitive impairment – encompassing 22 late-onset (LOD) and 31 early-onset depression (EOD), and 22 euthymic elders without cognitive impairment (controls). Participants underwent lumbar puncture for determination of CSF concentrations of Aβ1-42, T-tau, and P-tau. Cut-off scores for suspected AD were: Aβ1-42 < 416p g/mL, P-tau > 36.1 pg/mL and Aβ/P-tau ratio < 9.53 (O. V. Forlenza et al. 2015). Statistical analyses consisted of analyses of variance (ANOVA), analyses of covariance (ANCOVA), Bonferroni post-hoc tests, and Pearson's chi-squared tests. Results: ANCOVA (age and schooling as covariates) displayed statistically significant results with respect to CSF biomarkers’ profiles regardless of the socio-demographic divergencies previously identified by one-way ANOVA. Mean Aβ1-42 values (pg/mL) were: aMCI, 360.3 (p < 0.001); LOD, 486.6 (p < 0.001); EOD, 494.2 (p < 0.001); controls, 528.3 (p < 0.001); p< 0.05. Mean Aβ1-42/P-tau ratio: aMCI, 7.9 (p < 0.001); LOD 14.2 (p < 0.001); EOD, 15.3 (p < 0.001); controls, 17.1 (p < 0.001); p < 0.05. Post-hoc tests indicated that patients with aMCI showed significant differences in biomarker profile compatible with AD signature. Limitation: The main limitation is the relatively small sample. Conclusion: Our findings suggest that, distinctively from aMCI, cognitive impairment in LLD is not associated with AD's CSF pathological signature.